Application and Properties of CL‐20/HMX Cocrystal in Composite Modified Double Base Propellants. Issue 1 (8th October 2019) - Wu, Zongkai; Liu, Ning; Zheng, Wei; Chen, Junbo; Song, Xiuduo; Wang, Jiangning; Cui, Chang; Zhang, Dongxiang; Zhao, Fengqi
Abstract: The composite modified double base (CMDB) propellants containing 2, 4, 6, 8, 10, 12‐hexanitro‐2, 4, 6, 8, 10, 12‐hexaazatetracyclo[5.5.0.0 5, 9 .0 3, 11 ] dodecane (CL‐20), 1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocane (HMX) or CL‐20/HMX cocrystal were prepared by the solventless extrusion formation technique. The performances of CMDB propellants were evaluated by means of stability, sensitivity, combustion and mechanical experiments. Raman spectra analysis indicated the stability of CL‐20/HMX cocrystal is partially destroyed in the rolling process under 90 °C, 10 MPa. Methyl violet tests revealed that the colored time of CMDB propellants containing CL‐20/HMX cocrystal, CL‐20 or HMX are 77, 60, and 75 min, respectively. Burning rate tests shown that the burning rates of CMDB propellants containing CL‐20/HMX cocrystal, CL‐20 or HMX in the pressure range of 8 to 18 MPa, increased 1.82, 4.67, and 4.67 mm/s, with the pressure exponents 0.095, 0.306, and 0.346, respectively. Mechanical property tests revealed that the mechanical properties of CMDB propellant containing CL‐20/HMX cocrystal are inconsistent, but the tensile strength has improved compare with CMDB propellant containing CL‐20. These results suggest that CL‐20/HMX cocrystal is a potential material to solve the application problem of the safety performance and stability of the propellants containing CL‐20. Abstract :